ACCOUNTING AS A TOOL FOR ECONOMY IN GERMAN BUSINESS. - Matz, Adolph (The Accounting Review, 1940)
Abstract The article discusses several issues related to accounting as a tool for economy in German business. With the start of European hostilities, innumerable questions concerning industries, commerce, raw materials, and economy of the belligerent nations were raised in the daily press. Of particular interest was Germany, which through the innovation of its "Four-Year" Plan, had set out some years before to place its national economy as much as possible on a basis of self-sufficiency. Stringent foreign exchange laws, rigid economy, strict control over capital and labor, barter-trade with other nations, and rationing of food articles have long been regarded as measures foreign to American trade, business, and national policies. It is the purpose of the author in this article to present the development of that phase in the German business world, which on the one hand has made such rapid and important progress, and, on the other hand, has been called upon to help in the struggle for greater economy and for the success of the Four-Year Plan.